Epoxy/glass fibres composites for civil applications: Comparison between thermal and microwave crosslinking routes. (1st October 2017) - Colangelo, F.; Russo, P.; Cimino, F.; Cioffi, R.; Farina, I.; Fraternali, F.; Feo, L.
Abstract: Fiber-reinforced polymers (FRPs) have gained a growing interest for civil applications mainly for their lightness, corrosion resistance and high specific mechanical properties especially in terms of stiffness and strength. In this work, epoxy/glass fibres composite formulations, prepared by thermal and microwave assisted curing routes, are systematically characterized by thermal and mechanical tests. In particular the thermal curing is performed at room temperature and at 100 °C while the microwave conditions are set at 1500 W for 10 min. Calorimetric measurements demonstrate that these processing conditions allow to prepare samples with comparable crosslinking degree. The time and cost-saving microwave approach gives rise to cured FRPs with higher flexural stiffness but, expectedly, characterized by a network with a structure more inhomogeneous with respect to thermal crosslinked ones. Pull-out strength determination of all investigated epoxy composite systems joined to three different supports: a conventional concrete (CC), an artificial aggregate concrete (AAC) and a geopolymer (G), are performed to highlight their potential use for civil engineering applications. The experimental findings further support the use of microwave cured FRP samples especially with respect to the CC support. Highlights: Epoxy/glass fiber composites thermally and microwave cured are investigated. The use of microwaves enhances stiffness and structural inhomogeneity of products. Curing conditions do not influence pull-out strength of studied FRP from civil supports.